A multi-step estimation approach for optimal control strategies of interconnected systems with weakly connected topology. (February 2023) - Wang, Yan; Su, Rong; Lv, Mingsong; Guan, Nan
Abstract: This paper studies optimal linear quadratic regulation (LQR) problem of discrete-time interconnected systems (ISs) defined over a weakly connected graph. Subsystems in an IS share information based on the topology of the system. The main challenge of this work in comparison to the standard LQR problem, stems from that a subsystem may never acquire information from some other subsystems, due to the weakly connected topology. In this paper, a multiple-step estimation approach is proposed to analytically design the optimal controller for ISs with weakly connected topology. Also, the optimal value of the cost function is explicitly derived. Finally, the effectiveness of the proposed method is illustrated by simulations using a connected vehicle system.